Virological failure and associated factors among patients receiving anti-retroviral therapy in Ethiopia: A systematic review and meta-analysis - Sintayehu Asnakew; Getasew Legas; Amare Kassaw; Tigabu Munye Aytenew; Solomon Demis Kebede; Worku Necho Asferie; Netsanet Ejigu; Binyam Minuye Birhane; Yenework Mulu Tiruneh; Birhanu Mengist Munie; Bekalu Mekonnen Belay; Mengistu Ewunetu; et al. (BMJ Open)
Objective This study aimed to pool the prevalence of virological failure and associated factors.Design Systematic review and meta-analysis.Primary outcome measure Prevalence of virological failure.Secondary outcome measure Factors affecting virological failure.Analysis The extracted data were exported to STATA V.17 for statistical analysis. A random-effects DerSimonian-Laird model was used to compute the pooled prevalence of virological failure.Setting Ethiopia.Participants Patients receiving anti-retroviral therapy.Results A total of 51 primary studies with a sample size of 38, 789 participants were included in the final meta-analysis. The pooled prevalence of virological failure among patients receiving anti-retroviral therapy (ART) in Ethiopia was 15.95% (95% CI: 12.63, 19.27; I2=97.99%; p<0.001). Substance use (adjusted OR (AOR)=2.37, 95% CI: 1.28, 4.39), non-disclosure of HIV status (AOR=4.63, 95% CI: 3.51, 6.11), interruption of ART (AOR=2.61, 95% CI: 1.55, 4.40), poor adherence to ART (AOR=4.31, 95% CI: 2.73, 6.79), baseline CD4 cell count <200 cells/mm3 (AOR=2.65, 95% CI: 1.62, 4.33), baseline advanced WHO clinical stage (WHO clinical stages III and IV) (AOR=3.02, 95% CI: 1.67, 5.45), baseline viral load >1000 copies/mL (AOR=4.63, 95% CI: 2.60, 8.26), opportunistic infections (AOR=3.58, 95% CI: 2.58, 4.96) and TB-HIV coinfection (AOR=3.97, 95% CI: 2.41, 6.54) were significantly associated with virological failure among patients receiving anti-retroviral therapy in Ethiopia.Conclusions The pooled prevalence of virological failure among patients receiving anti-retroviral therapy was high in Ethiopia. Therefore, due attention should be given to patients with these identified factors. Moreover, we recommend researchers to conduct a triangulated study that can address additional factors associated with virological failure.PROSPERO registration number The protocol was registered with the Prospero database (PROSPERO, 2024: CRD42024512411).